The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0101-20612005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Melão minimamente processado: um controle de qualidade

Abstract: RESUMOO processamento mínimo tem sido descrito como a manipulação, preparo, embalagem e distribuição de produtos agrícolas, através de procedimentos como a seleção, limpeza, lavagem, descascamento e corte, que não afetem as suas características organolépticas e agreguem valor aos mesmos, resultando em produtos naturais, práticos, cujo preparo e consumo requerem menos tempo, atendendo às exigências da vida moderna. A finalidade dos alimentos minimamente processados e refrigerados é proporcionar ao consumidor um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
0
6
1
7
Order By: Relevance
“…The TS average values increased beyond the sixth day of storage on the PS-PVC packaging, with average of 5.96 mg for glucose, at time 0, and 9.28 mg of glucose on the last day of storage, in guavas stored in PS-PVC packaging, without any significant differences. Damasceno et al (2005) did not find significant differences in TS levels of minimally processed honeydew melons stored at 4 °C, however, when they were stored at 15 °C a significant reduction was observed throughout the experiment. The results from the RS analysis found statistical evidence of an interaction between the type of packaging, sanitization method and storage time.…”
Section: Consumers Surveycontrasting
confidence: 62%
See 4 more Smart Citations
“…The TS average values increased beyond the sixth day of storage on the PS-PVC packaging, with average of 5.96 mg for glucose, at time 0, and 9.28 mg of glucose on the last day of storage, in guavas stored in PS-PVC packaging, without any significant differences. Damasceno et al (2005) did not find significant differences in TS levels of minimally processed honeydew melons stored at 4 °C, however, when they were stored at 15 °C a significant reduction was observed throughout the experiment. The results from the RS analysis found statistical evidence of an interaction between the type of packaging, sanitization method and storage time.…”
Section: Consumers Surveycontrasting
confidence: 62%
“…However, counting these microorganisms at low temperatures such as 3 °C, for example, allows inclusion of psychrophilic bacteria in those counts and, even though there is no specific legislation for these bacteria, it is commonly accepted that food products which contain microbial counts around 10 5 to 10 6 CFU.g -1 are considered inappropriate for human consumption due to loss experiment, merely in minimally processed guavas stored in PS-PVC packaging for both types of sanitization processes, and, moreover, these values were higher after the sixth day of storage. Damasceno et al (2005) also observed an increase in this feature, throughout the experiment, in minimally processed honeydew melons stored at 15 °C (Table 3).…”
Section: Physicochemical Analysismentioning
confidence: 58%
See 3 more Smart Citations